Regional Sukuk Issuance Strategy (Islamic Municipal Bonds) in Indonesia - Taufiq Hidayat; Hermanto J. Siregar; Ahmad Affandi Mahfudz; Rifki Ismal; Krisma Muldan (ADI Publisher, 2022)
Islamic Municipal Bonds (sukuk) is one out of fund sources that can be used by regions for financing regional development projects. However, discussion about the Islamic Municipal Bonds issuing in Indonesia are still in the form of discourse. The aims of this study are to analyze the problem of issuing Islamic Municipal Bonds in Indonesia, and to find the best solutions and strategies for launching sukuk in Indonesia. The method that used in this research was the concept of Tawhidy String Relation (TSR) combined with the Delphi and the Analytical Network Process (ANP). The 2 (two) main problems that become obstacles and also root causes in the publishing of Islamic Municipal Bonds are low literacy of sharia and legal and regulatory barriers. The implication of this research was that sharia economic actors could improve economic and financial literacy of sharia. Meanwhile, regarding legal and regulatory issues, the government must encourage the creation of harmonization of laws and implementing regulations that provide legal certainty and accelerate the implementation of the issuance of regional sukuk in Indonesia. Finally, by publishing the Islamic Municipal Bonds, there is an increase in cross-sectoral economic activities based on sharia economics.